Global Research Trends on Factors Affecting Tuberculosis (TB) Adherence and Dropout: A Bibliometric Study - Risnawati Risnawati; Rosihan Adhani; Mohamad Isa; Nia Kania; Silvia Kristanti Tri Febriana (Universitas Malahayati Lampung, 2024)
ABSTRACT Tuberculosis (TB) remains one of the significant global health challenges, especially in resource-limited countries. Adherence to TB treatment is key to successful therapy and preventing the emergence of drug resistance. However, dropout rates or discontinuation of treatment before completion remains a major problem that needs to be addressed. This study aims to analyze global trends in research focusing on factors affecting TB treatment adherence and dropout through a bibliometric approach. Using the Publish or Perish application, relevant scientific articles with keywords such as treatment adherence, tuberculosis, treatment dropout, and influencing factors were searched from 2017 to 2024. A total of 50 articles from Google Scholar were further analyzed to identify by publication year, country, publisher, citation, and article type. The data was then processed using VOSviewer to visualize the relationship between keywords and research trends through Network Visualization, Overlay Visualization, and Density Visualization. The results of the analysis showed that Indonesia is the country with the highest number of publications, demonstrating a great commitment in addressing the TB challenge. Articles published in reputable journals, especially those adopting systematic and meta-analysis approaches, show great impact with a high number of citations. Bibliometric visualizations reveal that the focus of research lies on factors such as treatment, adherence, health workers, and access. In addition, family and community support was also found to be an important element in ensuring treatment adherence. In conclusion, this study emphasizes the need for a comprehensive and collaborative approach in improving TB treatment adherence and preventing dropouts. Further research in this area is needed to address existing gaps and develop more effective strategies in the fight against TB. Keywords: Treatment Adherence, Tuberculosis, Dropout, Influencing Factors, Health Worker